Catalyst‐Free Synthesis of α‐Functionalized 2H‐Chromenes in Water: A Tandem Self‐Promoted pseudo‐Substitution and Decarboxylation Process. Issue 17 (7th August 2019) - Jiang, Chunhui; Chen, Yayun; Zhang, Hongkui; Tan, Jian‐Ping; Wang, Tianli
Abstract: A catalyst‐free decarboxylative reaction between β‐keto acids and 2 H ‐chromene acetals in water was developed. This reaction featured a broad substrate scope and easily obtainable starting materials to afford α‐functionalized 2 H ‐chromenes in high yields. The synthetic value of this protocol was also demonstrated by the scale‐up synthesis and versatile conversions of the title product into other useful compounds. In addition, control experiments indicated that water was essential for the reactivity. Mechanistic studies further revealed that the reaction proceeded through a self‐promoted tandem pseudo ‐substitution and decarboxylation process. Abstract : Focused on self‐promotion : An environmentally benign approach for the preparation of α‐functionalized 2 H ‐chromenes with carbonyl moieties is described. This reaction can be performed in water under ambient conditions, and the β‐keto acids serve as not only as acrylic donors but also acidic self‐promoters for this catalyst‐free transformation. A wide range of 2 H ‐chromene acetals and β‐keto acids show generally good reactivities, furnishing the desired 2 H ‐chromenes derivatives in good to excellent yields.